2015
DOI: 10.1016/j.ypmed.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Personal goals and changes in life-space mobility among older people

Abstract: Mobility in Old Age study (LISPE), which was conducted between 2012 and 2014, the participants responded to the Life-Space Assessment and Personal Project Analysis in addition to questions on socio-demographics and health. Data were analyzed using generalized estimation equation models. The results showed that goals indicating a desire to be active in daily life, to stay mentally alert, and to exercise were associated with higher lifespace mobility, and that the associations remained over the follow-up years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 29 publications
2
32
0
5
Order By: Relevance
“…Consequently, they may be better able to maintain their physical activity over time than those with lower-extremity physical limitations who reported more environmental facilitators. However, it is also possible that over time participants modified their perceptions of the environment due to declining physical function and subsequent changes in goals and valuation of meaningful activities [42,47]. Unfortunately, we could not take this into account in the analyses due to lacking data on perceived environmental facilitators at the follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they may be better able to maintain their physical activity over time than those with lower-extremity physical limitations who reported more environmental facilitators. However, it is also possible that over time participants modified their perceptions of the environment due to declining physical function and subsequent changes in goals and valuation of meaningful activities [42,47]. Unfortunately, we could not take this into account in the analyses due to lacking data on perceived environmental facilitators at the follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Temme et al (2008) found that some abstract motivations such as hedonism and power influence transportation mode choice. Saajanaho et al (2015) found that the older adults' spatial extent of mobility in daily life (defined as Life-space mobility) is influenced by personal goals. For example, older adults who had reported personal goals such as maintaining functioning, staying mentally alert, activeness in daily life, and meeting other people, had larger life-space mobility compared to those not reporting such goals.…”
Section: Research Gapsmentioning
confidence: 99%
“…Nessas unidades, o profissional de saúde deve estimular a população idosa a desenvolver e praticar um estilo de vida ativo e saudável. 26 A maioria dos idosos do presente estudo demonstrou possuir como renda até dois salários mínimos e baixa escolaridade (Tabela 1). Estudos mostram que idosos com baixo poder aquisitivo e menor escolaridade estão associados a acesso limitado a atividade física, pior percepção de saúde e estado funcional, somado à vizinhança frequentemente insegura com menor oferta para transportes.…”
Section: Discussionunclassified
“…Estudos mostram que idosos com baixo poder aquisitivo e menor escolaridade estão associados a acesso limitado a atividade física, pior percepção de saúde e estado funcional, somado à vizinhança frequentemente insegura com menor oferta para transportes. [26][27][28] Esses resultados vão ao encontro dos achados da presente pesquisa em relação às barreiras para a prática de atividade física dos idosos (Tabela 3), cujos recursos financeiros e o ambiente insuficientemente seguro parecem afetar a prática de atividade física dos idosos. A barreira menos frequente foi quanto à jornada de estudo extensa, resultado esperado, já que essa atividade não está muito presente na rotina do perfil desses idosos.…”
Section: Discussionunclassified